Moringa oleifera Flower Extract Suppresses the Activation of Inflammatory Mediators in Lipopolysaccharide-Stimulated RAW 264.7 Macrophages via NF-κB Pathway - Woan Sean Tan; Palanisamy Arulselvan; Govindarajan Karthivashan; Sharida Fakurazi (Mediators of Inflammation)
Aim of Study. Moringa oleifera Lam. (M. oleifera) possess highest concentration of antioxidant bioactive compounds and is anticipated to be used as an alternative medicine for inflammation. In the present study, we investigated the anti-inflammatory activity of 80% hydroethanolic extract of M. oleifera flower on proinflammatory mediators and cytokines produced in lipopolysaccharide- (LPS-) induced RAW 264.7 macrophages. Materials and Methods. Cell cytotoxicity was conducted by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Nitric oxide (NO) production was quantified through Griess reaction while proinflammatory cytokines and other key inflammatory markers were assessed through enzyme-linked immunosorbent assay (ELISA) and immunoblotting. Results. Hydroethanolic extract of M. oleifera flower significantly suppressed the secretion and expression of NO, prostaglandin E2 (PGE2), interleukin- (IL-) 6, IL-1β, tumor necrosis factor-alpha (TNF-α), nuclear factor-kappa B (NF-κB), inducible NO synthase (iNOS), and cyclooxygenase-2 (COX-2). However, it significantly increased the production of IL-10 and IκB-α (inhibitor of κB) in a concentration dependent manner (100 μg/mL and 200 μg/mL). Conclusion. These results suggest that 80% hydroethanolic extract of M. oleifera flower has anti-inflammatory action related to its inhibition of NO, PGE2, proinflammatory cytokines, and inflammatory mediator’s production in LPS-stimulated macrophages through preventing degradation of IκB-α in NF-κB signaling pathway.